2023
DOI: 10.3390/biomedicines11020606
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilaments and OCT Metrics Predict EDSS-Plus Score Progression in Early Relapse-Remitting Multiple Sclerosis

Abstract: (1) Background: Early disability accrual in RRMS patients is frequent and is associated with worse long-term prognosis. Correctly identifying the patients that present a high risk of early disability progression is of utmost importance, and may be aided by the use of predictive biomarkers. (2) Methods: We performed a prospective cohort study that included newly diagnosed RRMS patients, with a minimum follow-up period of one year. Biomarker samples were collected at baseline, 3-, 6- and 12-month follow-ups. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A customized treatment strategy must start with the early detection of patients who are at risk for disability. Previous studies have found that factors including cortical fractal dimension, lesion on magnetic resonance imaging (MRI), and retinal measurements are associated with disability after optic neuritis (7)(8)(9)(10)(11)(12)(13)(14). However, single factors, such as current clinical and paraclinical measures, are not sufficient to reliably predict the risk of disability.…”
Section: Introductionmentioning
confidence: 99%
“…A customized treatment strategy must start with the early detection of patients who are at risk for disability. Previous studies have found that factors including cortical fractal dimension, lesion on magnetic resonance imaging (MRI), and retinal measurements are associated with disability after optic neuritis (7)(8)(9)(10)(11)(12)(13)(14). However, single factors, such as current clinical and paraclinical measures, are not sufficient to reliably predict the risk of disability.…”
Section: Introductionmentioning
confidence: 99%